Quantum theory from small to large scales: lecture notes of the Les Houches Summer School: Volume 95, August 2010 - Fröhlich, Jürg; Fröhlich, Jürg; Salmhofer, Manfred; Cugliandolo, Leticia F. (Oxford University Press, 2012)
This title collects lecture courses and seminars given at the Les Houches Summer School 2010 on 'Quantum Theory: From Small to Large Scales'. It reviews the state-of-the-art developments in this field by touching on different research topics from an interdisciplinary perspective.
Selected conference papers. - Includes bibliographical references. - Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012)
Keywords: Konferenzschrift; Quantenphysik